2009 IEEE International Symposium on Information Theory 2009
DOI: 10.1109/isit.2009.5205786
|View full text |Cite
|
Sign up to set email alerts
|

Multi-stage decoding of LDPC codes

Abstract: In this paper we present a three-stage decoding strategy that combines quantized and unquantized belief propagation (BP) decoders with a mixed-integer linear programming (MILP) decoder. Each decoding stage is activated only when the preceeding stage fails to converge to a valid codeword. The faster BP decoding stages are able to correct most errors, yielding a short average decoding time. Only in the rare cases when the iterative stages fail is the slower but more powerful MILP decoder used. The MILP decoder i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…1 Our initial experiments indeed show that girth-10 codes have a lower error floor compared with girth-6 and girth-8 codes of the same length and rate. This result, and other details about the codes found using our algorithm, will be discussed in depth in a future paper [19].…”
Section: Introductionmentioning
confidence: 77%
“…1 Our initial experiments indeed show that girth-10 codes have a lower error floor compared with girth-6 and girth-8 codes of the same length and rate. This result, and other details about the codes found using our algorithm, will be discussed in depth in a future paper [19].…”
Section: Introductionmentioning
confidence: 77%
“…Feldman and his collaborators showed that, for binary codes used over symmetric channels, a relaxed version of the maximum likelihood (ML) decoding problem can be stated as a linear program (LP). Considering graph-based 1 low-density parity-check (LDPC) codes, work by Feldman et al and later authors [4] [5] [6] [7] demonstrates that the bit-error-rate performance of LP decoding is competitive with that of standard sum-product (and min-sum) belief propagation (BP) decoding. Furthermore, LP decoding comes with a certificate of correctness (ML certificate) [3] -verifying with probability one when the decoder has found the ML codeword.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the notable works include augmented belief propagation [17], informed dynamic scheduling [18], multi-stage decoding [19], averaged decoding [20], and the use of post-processing to lower the error floors [21], [22]. While all these schemes certainly provide performance enhancements in the error floor, all of them require either a considerable increase in decoding complexity due to the modifications and post-processing or are restricted to a particular code whose structure is well known.…”
Section: Finite Precision Iterative Decoding and The Error Floor:mentioning
confidence: 99%